This Won’t Last Forever: Benefits and Costs of Anticipatory Nostalgia - Zhou, Xinyue; Huang, Rong; Batcho, Krystine; Ye, Weiling (Frontiers in Psychology, 2020)
What helps consumers extract the greatest happiness from their experiences? The current investigation is the first to introduce to the consumer literature the construct of anticipatory nostalgia, defined as missing aspects of the present before they vanish in the future. While personal nostalgia involves fond memories and longing for what has already been lost, anticipatory nostalgia involves missing what has not yet been lost. In four studies, we show that marketing communications can elicit anticipatory nostalgia, and this emotion can either enhance or reduce consumer enjoyment of the experience, depending on the experience valence or the individual’s level of life satisfaction. Specifically, mediated by anxiety, anticipatory nostalgia decreased enjoyment and positive affect in pleasant situations, but it enhanced enjoyment and affect in unpleasant circumstances. Study 4 extended the paradigm to a real-life setting and showed that the impact of anticipatory nostalgia on enjoyment and meaningfulness can last as long as eight hours after the manipulation.